1999
DOI: 10.1152/ajpendo.1999.277.6.e976
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-specific activation of NAD(P)H oxidase in aortas of exogenously hyperinsulinemic rats

Abstract: To examine the effects of chronic hyperinsulinemia on vascular tissues, we examined the production of superoxide anion (O(-2)) in the aortic tissues of control and exogenously hyperinsulinemic rats performed by the implantation of an insulin pellet for 4 wk. O(-2) production by aortic segments from hyperinsulinemic rats was 2. 4-fold (lucigenin chemiluminescence method) and 1.7-fold (cytochrome c method) of that of control rats without any differences in O(-2) degrading activities in aortic tissues, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 32 publications
(32 reference statements)
3
58
0
Order By: Relevance
“…However, the TNF-induced ROS production was significantly reduced by pretreatment with DPI (10 M) an inhibitor of flavincontaining enzymes such as NADPH oxidase (26) or by the NADPH oxidase inhibitor apocynin (10 M) (27,28). Furthermore, in separate experiments, we confirmed the effect of DPI by adding this agent 30 min after TNF.…”
Section: Nadph Oxidase Is the Main Source Of Tnf-induced Ros Productisupporting
confidence: 56%
See 1 more Smart Citation
“…However, the TNF-induced ROS production was significantly reduced by pretreatment with DPI (10 M) an inhibitor of flavincontaining enzymes such as NADPH oxidase (26) or by the NADPH oxidase inhibitor apocynin (10 M) (27,28). Furthermore, in separate experiments, we confirmed the effect of DPI by adding this agent 30 min after TNF.…”
Section: Nadph Oxidase Is the Main Source Of Tnf-induced Ros Productisupporting
confidence: 56%
“…Furthermore, we demonstrate that the NADPH oxidase complex was the main source of ROS in ASM cells under TNF stimulation. Indeed, incubation of ASM cells with two structurally different pharmacological inhibitors of NADPH oxidase (DPI (26) and apocynin (27,28)) significantly reduced TNFinduced ROS production, while the substrate NADPH significantly increased it. Moreover, inhibitors of mitochondrial respiratory chain, NO synthase, cyclooxygenase, and xanthine oxidase had no effect on TNF-induced ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance is known to affect the physiology of various organs, including skeletal muscles, adipose tissue and liver. Furthermore, recent basic and clinical studies have described the direct effects of insulin resistance at the level of the vessel wall [37][38][39][40] . LpL is known to exist in endothelial cells, showing activity, and LpL was also reported to exist on the coronary lumen surface 41) .…”
Section: Significance Of a Low Preheparin Lpl Mass Concentration In Smentioning
confidence: 99%
“…Recently, insulin resistance was reported to affect not only skeletal muscle and the liver but also vessel walls [31][32][33][34][35] . Kashiwagi A et al [36][37][38][39] reported that insulin resistance/hyperinsulinemia causes endothelial dysfunction and smooth muscle cell proliferation through the pathway of oxidative stress or inflammation, and consequently insulin resistance promotes atherosclerosis. In this study, there was a significant relationship between HOMA-IR as a marker of insulin resistance and percent plaque volume; however, multivariate analysis revealed that HOMA-IR did not select independent variables for percent plaque volume.…”
Section: Significance Of Ms For Plaque Formation In Early Stage Coronmentioning
confidence: 99%